THE CONTRIBUTION OF ARM MUSCLE STRENGTH AND BACK MUSCLE STRENGTH TO VOLLEYBALL TOP SERVE SKILLS - Rizky, Oddie Barnanda; Raibowo, Septian; Prabowo, Andika; Ilahi, Bogy Restu; Permadi, Andes (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
This study aims to determine how much the contribution of arm and back muscle strength to volleyball serve in Semester 1 Physical Education students of Bengkulu University. This study used statistics with product moment correlation techniques and multiple correlations. This research is objective, and the sample consists of 30 students of Semester 1 Physical Education of Bengkulu University, who were taken with a total sampling technique. There is a significant relationship between X1 and X2 with Y, because the result of the data rcalculate = 0.82 is greater than rtable = 0.361. There is a contribution between arm muscle strength, back muscle strength on volleyball top serve by 67% because K = r2 x 100% = 67%.